2006
DOI: 10.1152/ajplung.00282.2005
|View full text |Cite
|
Sign up to set email alerts
|

All-transretinoic acid modulates radiation-induced proliferation of lung fibroblasts via IL-6/IL-6R system

Abstract: Although high-dose thoracic radiotherapy is an effective strategy for some malignancies including lung cancers and malignant lymphomas, it often causes complications of radiation fibrosis. To study the mechanism initiating tissue fibrosis, we investigated irradiation-induced cytokine production from human lung fibroblastic cells and found that IL-6 production was stimulated by irradiation. IL-6 is an autocrine growth factor for human myeloma cells, and retinoic acid is reported to inhibit their growth. Thus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 45 publications
11
66
2
Order By: Relevance
“…We demonstrated that ATRA induced proliferation of irradiated AFT024 cells as shown by immunohistochemistry, cell cycle analysis, and gene expression studies. Previous studies in fetal rat hepatocytes and HepG2 cell lines [11], as well as in irradiated acute promyelocytic leukemia cell-line HL-60 [12] and human lung fibroblast cells [13], have demonstrated the antiproliferative and differentiating effects of ATRA. To our knowledge, this is the first report that ATRA may induce proliferation of irradiated stromal cells.…”
Section: Discussionmentioning
confidence: 96%
“…We demonstrated that ATRA induced proliferation of irradiated AFT024 cells as shown by immunohistochemistry, cell cycle analysis, and gene expression studies. Previous studies in fetal rat hepatocytes and HepG2 cell lines [11], as well as in irradiated acute promyelocytic leukemia cell-line HL-60 [12] and human lung fibroblast cells [13], have demonstrated the antiproliferative and differentiating effects of ATRA. To our knowledge, this is the first report that ATRA may induce proliferation of irradiated stromal cells.…”
Section: Discussionmentioning
confidence: 96%
“…XRT activates inflammatory pathways in several cell types, including endothelial cells, macrophages and fibroblasts, that potentially participate in the initiation and amplification of cardiac toxicity (7)(8)(9)(10). Interleukin (IL)-1 is the prototypical inflammatory cytokine activated in response to tissue injury (11)(12)(13) and has been found to be increased in the heart Thoracic X-ray therapy (XRT), used in cancer treatment, is associated with increased risk of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…In post-irradiation analysis, immunofluorescence stainings were performed to detect the production of IL-6 and c-H2AX [17,18]. As mentioned before, the autocrine induction of IL-6 in PC12 under ionizing radiation was reported.…”
Section: Immunofluorescence Stainingsmentioning
confidence: 92%